Conformational Disorder of Membrane Peptides Investigated from Solid-State NMR Linewidths and Lineshapes - Su, Yongchao (2011)
A challenge in the application of solid-state NMR spectroscopy to membrane peptides and proteins is the relatively broad linewidths compared to solution NMR spectra. To understand the linewidth contributions to membrane protein NMR spectra, we have measured the inhomogeneous and homogeneous linewidths of several well-studied membrane peptides under immobilized conditions. (13)C T(2) relaxation times of uniformly (13)C-labeled residues show that the homogeneous linewidths of the peptides are comparable to those of crystalline model compounds under identical (1)H decoupling and magic-angle-spinning conditions, indicating that the homogeneous linewidths are determined by conformation-independent factors, including residual dipolar coupling, J coupling and intrinsic T(2) relaxation. However, the membrane peptides exhibit larger apparent linewidths than the crystalline compounds, indicating conformational disorder. A cationic cell-penetrating peptide, the human immunodeficiency virus TAT, exhibits the largest apparent linewidths, which are about 5-fold larger than the homogeneous linewidths, while the transmembrane helix of the influenza M2 peptide and the β-hairpin antimicrobial peptide PG-1 show moderately larger apparent linewidths than the crystalline compounds. These results are consistent with the random coil nature of the TAT peptide, which contrasts with the intramolecularly hydrogen-bonded M2 and PG-1. Cross peak lineshapes of 2D double-quantum correlation spectra show that the conformational disorder can occur at the residue level and can result from three origins: lipid-peptide interaction, intrinsic conformational disorder encoded in the amino acid sequence, and sidechain rotameric averaging. A particularly important lipid-peptide interaction for cationic membrane peptides is guanidinium-phosphate ion pair interaction. Thus, NMR linewidths and lineshapes are useful for understanding the conformational disorder of membrane peptides and proteins.